Manuscrits de la Ribagorça vs. manuscrits del Matarranya: un assaig de dialectologia diacrònica. - Giralt Latorre, Javier; Moret Oliver, María Teresa (Zeitschrift für Katalanistik, 2021)
Over the last 25 years, the research carried out on the use of northwestern scripta (written medieval Aragonese) in 14 and 15century documentation found in La Franja (Aragon), has provided us with very interesting data. However, these works have focused on describing the written language of a set of manuscripts, rather than on comparing documents originating from different areas in this territory. The aim of this paper is to confirm that there are differentiating features between the manuscripts from Ribagorza (Huesca) and those from Matarraña (Teruel), which demonstrate that diatopic variation already existed in those times, and also give us an insight into what the living language of that time was like in those regions. Always, of course, with the caution one must apply when attempting to establish the features of different dialects that existed in medieval times.